An Intelligent Tracking System: Application to Acute Respiratory Tract Infection (TrackARTI) - Ertugrul, Duygu Celik; Elci, Atilla; Bitirim, Yiltan (IEEE, 2017)
This article proposes an Intelligent Tracking System for Acute Respiratory Tract Infection (TrackARTI) via a smart mobile for monitoring disease term of 0-6 age group child patients remotely (e. g. home, clinics). It is possible to maximize the quality of life of the child patients and decrease parental anxiety by keeping the child under control during monitoring stage and achieve a proper distant diagnose by the patient's clinician. This is possible with the designs of intelligent M-Health systems that can be used for diagnosing and monitoring the child patients away from hospitals by presenting the instant medical data to their registered doctors. Intelligent M-Health systems require strong knowledge management technology and ease of extension to provide information from additional medical tools. With the contribution of intelligent M-Health systems, it is possible to infer new facts from the certain gathered medical data during examination from child patients. This article mentions an intelligent and easy medical data gathering system that can be used by pediatricians or parents any time. In addition, the system has its own inferencing mechanism that involves two main steps; inferencing on image processing and Semantic Web rule knowledge base.
41st IEEE Annual Computer Software and Applications Conference (COMPSAC) -- JUL 04-08, 2017 -- Torino, ITALY
Keywords: Smart Mobile Systems; Acute Respiratory Tract Infection Monitoring System; Semantic Web Rule Knowledgebase; e-Health Systems; Inferencing